Landscape transformation under the Gåsbreen glacier recession since 1899, southwestern Spitsbergen - Ziaja Wiesław (Polish Polar Research, 2016)
Landscape changes of the Gåsbreen glacier and its vicinity since 1899 are described. Maps at 1:50 000 scale of changes of the glacier’s elevation and extent for the periods 1938–1961, 1961–1990, 1990–2010, and 1938–2010 are analyzed in comparison with results of the authors’ field work in the summer seasons 1983, 1984, 2000, 2005 and 2008. During all the 20th century, the progressive recession of the glacier revealed in a dramatic decrease in the thickness of its lower part, with a small reduction of its area and length. However, further shrinkage produced significant shortening and reduction in area which resulted in final decline of the Goësvatnet glacial dammed lake in 2002. Hence, the lowest (and very thick, up to 150–160 m) part of the former glacier tongue and dammed lake were transformed into a new terraced river valley south of the glacier and a typical marginal zone with glacial landforms north of the glacier. Since 1961, the equilibrium line altitude of the Gåsbreen glacier has risen from ca 350 to ca 500 m a.s.l. and now is located below the very steep rocky walls of the Mehesten mountain ridge, 1378 m a.s.l. Hence, the glacier is being fed by snow avalanches from these rocky walls and much more snow melts during the warmer summer seasons, stimulating a quicker recession of the lowest part of the glacier. This recession may be stopped only by significant climate cooling or increase in snow.